2011
DOI: 10.1590/s1678-91992011000400016
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal activity of venomous saliva from Rhynocoris fuscipes (Reduviidae) against Spodoptera litura and Helicoverpa armigera by microinjection and oral administration

Abstract: Abstract:Rhynocoris fuscipes is a potential predator of many economically important pests in India. In the present study, its venomous saliva (VS) was collected by milking and diluted with HPLC grade water to different concentrations (200, 400, 600, 800 and 1000 ppm). Microinjection of Rhynocoris fuscipes VS was more toxic than its oral administration in Helicoverpa armigera (cotton bollworm) and Spodoptera litura (tobacco cutworm). Thus, R. fuscipes VS was found to be toxic to third instar S. litura and H. ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Because reduviids can only ingest liquid food, the salivary secretions play a critical role in paralyzing and feeding of their prey. The toxic protein content of venomous saliva in reduviids varies with respect to males and females 38 . Records of adult female reduviids paralyzing their prey more rapidly than adult males reinstate the above fact 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Because reduviids can only ingest liquid food, the salivary secretions play a critical role in paralyzing and feeding of their prey. The toxic protein content of venomous saliva in reduviids varies with respect to males and females 38 . Records of adult female reduviids paralyzing their prey more rapidly than adult males reinstate the above fact 39 .…”
Section: Discussionmentioning
confidence: 99%
“…For CLC assemblies, reads with q-scores below 30 were trimmed and the reads assembled using minimum contig length of 150 bp, minimum similarity to join contig 0.95, and word (k-mer) sizes of 21,24,29,34,44,54, and 64. For Trinity, which employs a fixed k-mer method, reads were assembled using the default trimming parameters and minimum contig length of 150 bp.…”
Section: Methodsmentioning
confidence: 99%
“…and peiratine ( Catamiarus brevipennis ) assassin bugs, but with doses that are likely substantially higher (2–9 μL of crude venom per gram of insect tissue) [ 46 , 111 , 140 , 143 ]. While Edwards [ 6 ] found that P. rhadamanthus venom had no effect when applied topically or orally to flies and cockroaches, both Sahayaraj and Muthukumar [ 143 ] and Sahayaraj and Vinothkanna [ 143 ] found that adding venom of Rhynocoris sp. diluted approximately 1:1000 to the feed of caterpillars over 96 h was sufficient to cause death.…”
Section: Diversification Of Venom Pharmacology In the Evolution Ofmentioning
confidence: 99%